Design and Optimization of Radial Turbines for Waste Heat Recovery Applications - Shashank Gupta (International Journal of Mechanical Dynamics and Systems Analysis, 2024)
Waste heat recovery (WHR) offers a compelling way to improve sustainability and energy efficiency in several different industrial sectors. In waste heat recovery (WHR) systems, radial turbines are essential because they capture waste heat and transform it into useful mechanical or electrical energy. A thorough summary of the design and optimization concepts guiding radial turbines for WHR applications is given in this review article. After outlining the basic concepts of thermodynamics and fluid dynamics that underpin radial turbine operation, the article explores the complexities of turbine design. It examines important factors that have an impact on turbine performance and efficiency, including material choice, structural integrity, and aerodynamic design. In addition, the review clarifies the different performance optimization approaches used in the design of radial turbines, from experimental validation procedures to computational fluid dynamics (CFD) simulations. Comprehensive discussions are also held regarding advanced optimization techniques, such as surrogate modeling and multi-objective optimization. The article illustrates the various uses of radial turbines in WHR in sectors like power generation, petrochemical, and automotive through several case studies and real-world examples. Critical analysis is performed on performance metrics, problems faced, and lessons learned from these applications to extract important information for upcoming research and development projects.
Keywords: Computational fluid dynamics; Sustainability; Waste heat recovery; fluid dynamics; turbines